Oxo-β-lactams as promising scaffolds for protease inhibition and activity-based probing - Ruivo, Eduardo Figueiredo Pires (2015)
Tese de mestrado, Química Farmacêutica e Terapêutica, Universidade de Lisboa, Faculdade de Farmácia, 2014